2015
DOI: 10.1093/gerona/glv013
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy Among Adults Aged 65 Years and Older in the United States: 1988–2010

Abstract: Prescription medication use increased dramatically among older adults between 1988 and 2010. Contemporary older adults on multiple medications have worse health status compared with those on less medications, and appear to be a vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
329
5
18

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 474 publications
(407 citation statements)
references
References 24 publications
18
329
5
18
Order By: Relevance
“…In developed countries, polypharmacy among the elderly varied between 39% 5 and 45% of the population 6 . In Brazil, a study with elderly people living in the metropolitan area of the city of São Paulo found a prevalence of polypharmacy of 36.0% 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, polypharmacy among the elderly varied between 39% 5 and 45% of the population 6 . In Brazil, a study with elderly people living in the metropolitan area of the city of São Paulo found a prevalence of polypharmacy of 36.0% 2 .…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Polypharmacy has become more common among the elderly 4 and is related to several problems, including increased risk of being prescribed potentially inappropriate medications (PIMs), 5 which are delineated in several drug lists, such as the American Geriatrics Society Beers criteria. 6 Both polypharmacy and PIMs increase adverse drug events, worsen physical function, and result in excess health care utilization.…”
mentioning
confidence: 99%
“…The single greatest predictor of ADEs and high-risk prescribing is the number of medicines a person is taking [10]. With demographic ageing, there are increasing numbers of older people prescribed multiple medications for multiple co-existing medical conditions [11]. In New…”
Section: High-risk Prescribingmentioning
confidence: 99%